A patient with Factor V Leiden mutation who developed a Pulmonary Embolism and Deep Vein Thrombosis post Covid (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.
Keywords: Hospital Medicine; Case Report